DEVELOPMENT OF STUDENT WORKSHEETS REFERRING TO THE ADDIE MODEL - Risa Kumala Sari; Marleni; Jayanti (Universitas PGRI Palembang, 2024)
The development of Student Worksheets (LKPD) with the help of mentimeter on flat shape material for class V SD Negeri 1 Banyuasin 1, has the aim of being able to produce LKPD on flat shape material with the help of mentimeter which is valid, practical and has potential effects for class V students of SD Negeri 1 Banyuasin1. The type of research used by researchers in developing this LKPD is research and development, development refers to the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were elementary VA class students at SD Negeri 1 Banyuasin 1. Data collection techniques used in the research were interviews, questionnaires, tests and documentation. based on the results of research by validator experts from three fields, namely media, material, language, the developed LKPD media obtained a validity level of 91.51%, from media experts who were categorized as